Innovation, R&D and industrial Restructuring in Central and Eastern European Countries - Yegorov, I. (Наука та інновації, 2005)
The article deals with the problems of development of the R&D and innovation systems in the Central and Eastern European (CEE) countries. Despite evident positive results in economic transformation, these countries have serious problems in innovation sphere. In turn, lack of in!house R&D and innovation activities negatively affects the growth rates of national economies. Recent tendencies in innovation development in CEE countries are promising but the gap between them and developed EU countries is still substantial.